KAJIAN PENGEMBANGAN BAWANG MERAH PADA LAHAN BERKADAR LIAT TINGGI (VERTISOL) DENGAN PENAMBAHAN PUPUK ORGANIK - Agus Mulyadi Purnawanto; Gayuh Prasetyo Budi (Universitas Muhammadiyah Purwokerto, 2008)
The aim of this research was to study of onion development at land with high clay content by organic fertilizer aplication. The research was conducted in Dukuhwaluh village, Kembarang Sub-District, Banyumas District on February until September 2006. The research was arranged by Randomized Completely Block Design with four replications. The first factor of treatment was kind of soil (T) consist of Alfisol dan Vertisol soil; the second factor was dosage of organic fertilizer (P) consist of four levels i.e. P0 = without organic fertilizer , P1 = aplicated 5 tons /hectare organic fertilizer, P2 = aplicated 10 tons/hectare organic fertilizer and P3 = aplicated 15 tons/hectare organic fertilizer. Results of the study showed that there are possibility of using of vertisol soil by organic fertilizer aplication for onion development location. The dosage of organic fertilizer that can to support onion development was 15 tons/hectare minimal. Using of Alfisol soil with 15 tons/hectare organic fertilizer aplicated can give higher of yield than the treatment other.